The Design and Testing of a New Antitangling and Antisticking Knife for a Wet Clay Soil Environment - Guosheng Geng; Tailai Chen; Maohua Xiao; Chenshuo Xie; Cungan Tang (Agriculture)
Aiming at the problem that rotary tiller knife rollers are prone to entanglement with straw in the wet and sticky soil environment of rice fields in the middle and lower reaches of the Yangtze River in China, an antitangling and sticking cutter was designed. The cutter reduces knife roller entanglement in order to reduce rotary tiller energy consumption and improve work efficiency, and its effectiveness was verified through theoretical analysis, discrete element simulation, and field trials. The design’s validity was verified through theoretical analysis, discrete element simulation, and field tests. The blade inclination design was completed through motion force analysis, and the tool geometry was optimized with a 36.87° inclination baffle and staggered arrangement. A simulation model of the soil–straw–rotary tillage knife interaction was established and we used the discrete element method to analyze the variation in torque between the antisticking knife and the China standard rotary tillage knife (IT245) at four different cutter shaft rotational speeds. In the simulation, the average torque for the antisticking knives was smaller than that of the national standard rotary tillage knives, with reductions of 37.1%, 52.1%, 52.8%, and 50.0%, respectively, demonstrating a remarkable effect. Field tests showed that the average operational efficiency of the antisticking knife was 0.57 hm2/h, with an operation qualification rate of 95.72%. The average torque results from simulation (with and without the antisticking knife) and field tests were analyzed, yielding correlation coefficients of 0.994 and 0.973 for the change curves of average torque between the antisticking knife and the national standard rotary tillage knife. This result confirms the accuracy of the simulation model and the consistency between the simulation and field test results. This study can provide some references for the design and test of antisticking of rotary tillers.